Political Asylum as a Geopolitical Instrument: A Study of Defection and Its Implications for Foreign Policy - Puspitasari, Dyah Rosiana; Ibrahim, Fakhry Muhammad (Journal of Legal Contemplation, 2025)
Political asylum has long been a sensitive issue in international relations, especially when granted to defectors or figures labelled as traitors by their home countries. This study aims to analyze the shift in meaning and function of political asylum in modern international relations, explain the geopolitical impact of defection accompanied by the granting of asylum, examine the foreign policy responses of the country of origin and the asylum-granting country, and provide an understanding of the dynamics of diplomatic tensions and foreign policy strategies related to the practice of granting asylum. This study uses a normative (doctrinal) juridical method, with a conceptual approach, legislation, and case studies. The data sources used are secondary data obtained through literature studies, consisting of primary legal materials, and tertiary Legal Materials. The results of the analysis show that political asylum has evolved from mere protection against persecution to an instrument of negotiation and geopolitical influence. Granting asylum to defectors has been proven to worsen diplomatic relations between countries, but on the other hand it is also used as a strategy of political pressure on the defector's country of origin. Therefore, countries need to balance between their commitment to protecting human rights and national interests, especially amidst increasing multi-regional geopolitical tensions. It is recommended that international legal norms be strengthened to clearly regulate the boundaries between the right to protection of individuals and the potential for political exploitation of asylum practices.